The discourse about COVID-19: a study in the press of Italy, Spain and Germany - Reguero Sanz, Itziar (2021)
This research analyses the opinion articles about the COVID-19 published in the main newspapers of Italy, Spain and Germany. To this purpose, a qualitative inductive-deductive content analysis methodology has been used along two complementary phases. The first included the detailed analysis of the sample, and the second involved a method of comparative textual analysis using the Sketch Engine software. The results show the existence of some common issues about the virus, although with different approaches depending on the country: a certain vision marked by national politics in the Spanish case, an interpretative view in the case of Germany and a more social-humanistic perspective in the Italian dailies. A discourse contrary to generating panic is common in the three countries studied, but with a clear underestimation of the virus’ potential consequences in the first couple of months after the outbreak in Wuhan as regards the Spanish and Italian press.